(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The present study aimed at knowing the effect of using Round House Strategy in developing learning motivation and whether the effect varies by gender for the fifth graders in Lattakia. Where it was used the method of semi empirical, for that an educational program based on Round House Strategy was designed for Circulatory system unit of the science studies book to the fifth grade. To measure the learning motivation Kattamy(1989) scale was used. The sample consisted of (60) students males and females, who distributed equally on two groups, between experimental and the control. The study showed that using Round House Strategy led to improve motivation of the experimental group to high motivation, the differences were statistically significant at the level of (0.05) between the pre- and post tests in favor of the post test . The results assured that there were statistical significant differences between the experimental and control groups in the post test in favor of the experimental group. The study led to recommendation of using Round House Strategy in improving motivation in various materials and at different age stages.